PERAN GURU PPKn SEBAGAI MOTIVATOR DALAM PEMBENTUKAN KARAKTER TANGGUNGJAWAB PESERTA DIDIK DI SMAN 16 SURABAYA: PERAN GURU PPKn SEBAGAI MOTIVATOR DALAM PEMBENTUKAN KARAKTER TANGGUNGJAWAB PESERTA DIDIK DI SMAN 16 SURABAYA - Nurrohman, Miftahul Akbar (Universitas Negeri Surabaya (Unesa), 2023)
This study describes the role of Civics teacher as a motivator in the formation of students' responsibility character. The location of this research is SMAN 16 Surabaya, using a research method with a qualitative approach and descriptive research design. This research focuses on the role of Civics teachers in the formation of the character of responsibility in students with the application of the independent curriculum. The data collection techniques used are observation, interviews and documentation. Using B.F Skinner's Behaviorism learning theory where it is explained that learning is a change in behavior as a result of the interaction between stimulus and response. The results of this study indicate that the role of the teacher as a motivator in shaping the character of responsibility in students at SMAN 16 Surabaya is by (1) Providing positive reinforcement in the form of giving awards or rewards (2) Providing negative reinforcement in the form of punishment. The supporting factor for the implementation of these activities is a conducive classroom atmosphere or condition, then the inhibiting factor is when students still often underestimate the learning process delivered by the teacher because what students feel coming to school is just attendance. The obstacle is the dependence of students on their parents so that it hinders the process of forming the character of responsibility in students. Key Words : Role, Character, Responsibility.